The Factors Affecting Electric Vehicle Purchase Decisions of Consumers in Bangkok - Sadthong, Prarinya (Rajapark Journal, 2024)
The research aimed to investigate the influence of marketing mix factors, information awareness, and brand value on consumers' purchasing decisions regarding electric vehicles in Bangkok. Data were collected from 400 consumers who have bought and have never bought an electric car to drive in Bangkok through a questionnaire. Descriptive statistics, including percentages, means, and standard deviations, were employed to analyze the data. Inferential statistics involved multiple regression analysis. The results revealed that the majority of respondents were male (67.25%), aged 31-40 (40.0%), with educational levels beyond a bachelor's degree (42.50%), engaged in self-employment or private business (30.0%), had an average monthly income of 20,001-30,000 baht (33.0%), and were considering purchasing a car priced between 1,000,000-2,000,000 baht. Hypothesis testing results indicated that, overall, the study of marketing mix factors significantly influenced purchasing decisions. Specifically, the findings suggested that advertising through various media had the greatest impact on purchasing decisions. The study of information awareness factors had a significant overall influence on purchasing decisions, with the highest impact observed in knowledge about electric vehicles, facilitating the decision-making process. Additionally, the study of product brand value factors overall significantly influenced purchasing decisions, with the highest impact observed when the brand of electric vehicles was recognized globally.